Update breast cancer 2019 part 2 - Implementation of novel diagnostics and therapeutics in advanced breast cancer patients in clinical practice = Update Mammakarzinom 2019 Teil 2 - Implementierung neuer Diagnostika und Therapien bei Patientinnen mit fortgeschrittenem Brustkrebs in der klinischen Praxis - Janni, Wolfgang; Schneeweiss, Andreas; Schütz, Florian (Geburtshilfe und Frauenheilkunde, 2019)
The treatment of patients with advanced breast cancer has developed further in recent years. In addition to therapeutic progress in the established subgroups (hormone receptor and HER2 status), there are now therapies which are geared to individual molecular characteristics, such as PARP inhibitor therapy in BRCA-mutated patients. In addition to this, tests are being developed which are intended to establish additional markers within subgroups in order to predict the efficacy of a therapy. PI3K mutation testing in HER2-negative, hormone-receptor-positive tumours and PD-L1 testing of immune cells in triple-negative tumours are expected to become established in clinical practice in order to select patients for the respective therapies. With new therapeutic approaches, new adverse effects also appear. The management of these adverse effects, just as those of classical therapy (supportive therapy), is essential with the introduction of new treatments in order to preserve patientsʼ quality of life. Knowledge regarding measures to preserve and improve quality of life has significantly increased in recent years. Lifestyle factors should be taken into account, as should modern therapeutic methods. This review summarises the latest studies and publications and evaluates them in regard to the relevance for clinical practice.
Gesehen am 19.07.2019